Analysis of the Effect of Service Quality and Customer Satisfaction on Customer Loyalty Through Customer Engagement: Case Study of AHASS Workshop PT. Buana Jaya Lestari, Medan Sunggal - Muhammad Yuda Hendrawan; Aqwa Naser Daulay; Budi Harianto (Jurnal Manajemen Bisnis, 2024)
ABSTRACT The purpose of this study was to analyze the effect of service quality, satisfaction on customer loyalty through customer engagement AHHAS Workshop PT Buana Jaya Lestari. The sample in this study were 100 customers of AHHAS workshop PT Buana Jaya Lestari. Data collection was carried out through surveys using valid and reliable research instruments. Data analysis using path analysis assisted with the help of Smart PLS (Partial Least Square) software version 4.1.0.3. The results of this study indicate that customer satisfaction and customer engagement have a positive influence on customer loyalty, while service quality has no significant effect on customer loyalty. The novelty of this study appears in the finding of an insignificant effect of service quality on customer loyalty. AHHAS Workshop PT Buana Jaya Lestari needs to make efforts to improve service quality towards Customer Loyalty. AHASS workshops can make several efforts to improve the quality of its services, among others: Improve timeliness in completing services, speeding up customer waiting time, building trust with customers by providing quality service and trust with customers by providing quality service and integrity. with integrity.